ANTIMICROBIAL SUSCEPTIBILITY OF S. PNEUMONIAE STRAINS ISOLATED FROM CHILDREN WITH NASOPHARYNGEAL CARRIAGE - Mariya Malcheva; Iva Philipova; Ivan Simeonovski; Viktoriya Levterova; Nadyia Brankova; Todor Kantardjiev (Problems of Infectious and Parasitic Diseases, 2020)
Streptococcus pneumoniae colonises the nasopharynx of children and could cause life-threatening diseases. As a result of the implementation of conjugate vaccines worldwide the spread of vaccine serotypes has decreased. In Bulgaria PCV10 was introduced in 2010 followed by changes in the invasive clones carrying resistance genes. The aim of our study is to determine the serotype distribution and resistance patterns of isolates from children carriers after vaccination. A total of 834 children were tested for S. pneumoniae and 21% showed positive culture results. All isolates were genotyped with PCR. We found that 85% of the positive samples are from children attending kindergartens and schools. The most frequent serotypes/serogroups were 6C (20%) and 24B/F (11.5%), followed by 3 (8.6%), 11A/D (8%), 35F (6.9%), 19A (6.3%), 23A (6.3%) and 15A/F (6.3%). The susceptibility to β-lactams was high and there were strains showing intermediate susceptibility to benzylpenicillin. This study found 76 (44%) MDR strains non-susceptible to at least 3 antibiotic classes and the most common resistance pattern was erythromycin-clindamycin-tetracycline.